Manajemen Risiko: Konsep, Peran, Tujuan, dan Proses dalam Pengelolaan Organisasi untuk Meningkatkan Stabilitas dan Kinerja - Naila Zulfa; Irsyad, Irsyad; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Risk management is a systematic process essential for helping organizations identify, analyze, and control risks that can disrupt the achievement of their objectives. This article discusses the history of risk management, its basic concepts, objectives, and its role in organizational management. Using a literature review method, this article outlines various approaches and processes for effective risk management, such as risk identification, analysis, evaluation, and handling, as well as the importance of communication and monitoring in their implementation. Risk management is not only beneficial for minimizing losses but also for supporting better decision-making and improving corporate governance. With proper risk management implementation, organizations can be better prepared to face uncertainty and turn risk into an opportunity for sustainable growth.